2014
DOI: 10.7718/ijec.v8i1.748
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Chlorophyll a and b in the Seagrass Halodule in Central Visayas, Philippines

Abstract: Chlorophyll content of seagrass leaves varies among species and habitats byat least a factor of five, and shows plastic responses to seasonal variations in light availability as well as direct experimental manipulation. This study generally attempted to observe the relative amount of chlorophyll a, b content of Haloduleuninervis and Halodule pinifolia in Central Visayas, Philippines in relation tothese environmental factors which are: exposure, density, temperature, and lightintensity. Chlorophyll was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
2
0
5
Order By: Relevance
“…Thus, measuring chlorophyll is one of the important parameters in water. The comparison of the mean chlorophyll content in Halodule leaves from different environments, temperatures and light illustrate the adaptive limits of optical plasticity in seagrass leaves (Wagey 2013). In the research, Wagey (2013) found differences in the results of chlorophyll pigments showing that chlorophyll pigments vary greatly according to various conditions.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, measuring chlorophyll is one of the important parameters in water. The comparison of the mean chlorophyll content in Halodule leaves from different environments, temperatures and light illustrate the adaptive limits of optical plasticity in seagrass leaves (Wagey 2013). In the research, Wagey (2013) found differences in the results of chlorophyll pigments showing that chlorophyll pigments vary greatly according to various conditions.…”
Section: Discussionmentioning
confidence: 94%
“…Sebagai sumber makanan penting bagi banyak organisme, lamun memiliki pruduktivitas primer yang tinggi dan biasanya hidup di perairan dangkal hingga kedalaman kurang lebih 4 (empat) meter (Hitalessy et al, 2015). Di perairan dangkal, lamun dapat tumbuh membentuk hamparan padang serta mirip seperti tumbuhan ilalang di daratan yang dapat terdiri dari satu species (monospesific) dan beberapa jenis spesies (multispesific) yang disebut padang lamun (Wagey, 2013).…”
Section: Pendahuluanunclassified
“…Pada proses ini jenis lamun yang diambil kemudian diletakkan diatas papan dan diamati untuk mengetahui jenis, morfologi seperti bentuk daun, rizoma dan batang, dan akar dari sampel. Dan untuk identifikasi jenis lamun dilakukan dengan mengacu pada buku Panduan Pemantauan Padang Lamun COREMAP-CTI Lembaga Ilmu Pengetahuan Indonesia 2017 dan Hilamun (seagrass) (Wagey, 2013).…”
Section: Identifikasi Jenis Lamununclassified
“…Preparasi sampel daun lamun T. hemprichii dilakukan di Laboratorium Biologi, Gedung E, Fakultas Perikanan dan Kelautan, Universitas Diponegoro. Metode preparasi sampel dilakukan menurut Wagey (2013), prosedur yang dilakukan yaitu sampel daun lamun T. hemprichii digerus menggunakan mortar dan alu hingga halus kemudian ditimbang sebanyak 50 mg menggunakan timbangan analitik. Sampel yang sudah ditimbang dipindahkan ke tabung reaksi dan dilarutkan menggunakan Aseton 90% sebanyak 5 ml.…”
Section: Gambar 1 Lokasi Penelitianunclassified